ANALISIS KESESUAIAN MODUL AJAR IPAS DENGAN KOMPONEN KURIKULUM MERDEKA PADA KELAS V DI SD NEGERI 12 MEMPAWAH HILIR - Zaitun Naimah; Mutmainnah; Dessy Setyowati; Yuni Listiarini (STKIP Subang, 2026)
This study aims to analyze the alignment of the Grade V IPAS teaching modules at SD Negeri 12 Mempawah Hilir with the components of the Merdeka Curriculum. Using a descriptive qualitative method, the research examined four teaching modules through documentation analysis. The analysis focused on four components: general information, module objectives, usage design, and materials–assessment–references. Findings show that the modules generally comply with curriculum requirements. General information is complete, although the special-needs indicator is not included. The module objectives are present but some lack measurable indicators. The usage design is systematic, and the materials, assessment, and references align with the curriculum standards. Overall, the IPAS modules are appropriate for classroom use, although several components still require improvement.